Pedagogia universitária na área da saúde: perfil docente e proposta de formação em serviço - Alves, Luciene (2013)
Higher education in Brazil is marked by profound social and political change, but the pedagogical training of university teacher is not always carefully evaluated, or even encouraged, to improve the process of teaching and learning. Considering these aspects, the present study was aimed to determine the factors that influence the didactic and pedagogical teaching courses in the area of health, Federal University of Triangulo Mineiro, giving transparency to experiences, and trace an offer quality training that can contribute to the development of actions and by the faculty of the institution. The research was quantitative and qualitative character. Were administered questionnaires semistructured, observed a significant number of lessons, analyzed documents and reviewed the literature in this area. The research consisted of 35 (40.7%) and 367 teachers (36.33%) students five undergraduate health care. The search met all propositions of Resolution. 196, the National Agency of Sanitary Surveillance of the Ministry of Health In response to inquiries and the classroom observations, it is concluded that teachers were at different stages in their academic careers, were not followed in the institution pedagogically. Despite already having attended courses with imprint didactic teaching, they have been carried out in most cases outside the higher education institution (HEI) and in isolation. Furthermore, we found that there are also limitations with regard to the practical articulation of Institutional Documents; disproportionate appreciation of the research, to the detriment of other areas of expertise (especially education and extension), the indiscriminate use of lecture, despite the diversification media (educational resources); motivation and satisfaction with their professional activities; despite having limitations to work with interdisciplinary (was checked facility to integrate the content with values, habits, and professional conduct applicable to professional practice), the need to innovate in teaching strategies, with regard to the form of organization of classes and available resources in order to attain the cognitive, affective and psychomotor class that demanded; concern with content, both in regards to submission for adequacy curriculum, scientific reasoning and training; concern with evaluative processes in the classes observed, both in the analysis of activities as in the adequate direction for the results of the students and control skills. As for the students participating in the survey, the results showed, among other things, that students had little knowledge of the institutional tools; infrastructure influences on their motivation for their studies, extracurricular activity participation was low and the support that the University offers for studies and for planning teaching methodology is satisfactory. It was concluded, therefore, that the strengthening of institutional policies with ace adequacy gaps found, monitoring and pedagogical teaching teachers through training programs for permanent teachers are essential if one wishes to increase the positives identified and remedy possible limitations in the educational process.